Macroeconomic Determinants of Fintech Lending Disbursement in Indonesia: An ARDL Approach - Carissa Harjanti Putri; Wiku Suryomurti (LP2M IAIN Palopo, 2026)
This study aims to evaluate the macroeconomic determinants of fintech lending disbursement volume in Indonesia from January 2021 to August 2025. The variables analyzed include inflation, Outstanding SBSN, money supply (M2), exchange rate, and the Industrial Production Index (IPI). The research employs a quantitative approach using the Autoregressive Distributed Lag (ARDL) model on monthly time series data. Results indicate that the IPI is the sole variable with a significant positive impact on disbursement volume in both the short run and long run. Other monetary variables such as inflation, SBSN, M2, and exchange rates prove to have no statistically significant influence during the observation period. The Error Correction Term (ECT) value of -1.17 confirms a stable cointegration relationship with a very high speed of adjustment toward equilibrium. These findings emphasize that the fintech lending sector in Indonesia is demand-driven and highly dependent on real sector productivity. The growth of this industry is more sensitive to manufacturing performance than to traditional monetary indicator fluctuations. The government is advised to align digital economic policies with the strengthening of the national real industrial sector.